Revisiting neutrino and sneutrino dark matter in natural SUSY scenarios - Faber T. (2020)
We study natural supersymmetric scenarios with light right-handed neutrino superfields, and consider the possibility of having either a neutrino or a sneutrino as a dark matter candidate. For the former, we evaluate the possibility of having SUSY corrections on the ν4→ν γ decay rate, such that the NuStar bounds are relaxed. We find that corrections are too small. For sneutrino dark matter, we consider thermal and nonthermal production, taking into account freeze-out, freeze-in, and super-weakly interacting massive particles mechanisms. For the nonthermal case, we find that the νR can reproduce the observed relic density by adjusting the R-sneutrino mass and Yukawa couplings. For the thermal case, we find the need to extend the model in order to enhance sneutrino annihilations, which we exemplify in a model with an extended gauge symmetry. © 2020 authors. Published by the American Physical Society. Published by the American Physical Society under the terms of the "https://creativecommons.org/licenses/by/4.0/" Creative Commons Attribution 4.0 International license. Further distribution of this work must maintain attribution to the author(s) and the published article's title, journal citation, and DOI.